2023
DOI: 10.1094/pdis-09-21-1908-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Stem Canker Caused by Diaporthe tulliensis on Jasmine in Taiwan

Abstract: Diaporthe species can infect forest trees, ornamentals, and crops, causing root and fruit rots, stem cankers, leaf spots, etc. (Yang et al. 2018). In February 2021, about 10-20% of jasmine plants showing stem canker, foot rot, and wilting were observed in Changhua (24°01'57.7"N 120°34'54.7"E), Taiwan. The diseased plants initially showed chlorosis, leaf drop, and dieback. Sunken lesions were observed on the infected stem and kept expanding gradually. Eventually, plants wilted and black spots formed on the lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Firstly, chlorosis symptoms were appeared on the flowers and also showed that leaves become fall from the branches of the plant. The diseases were controlled by the help of molecular techniques and the chemical treatments [50]. Tagetes erecta is commonly known as the African marigold flowering plant which is cultivated as cosmopolitanly.…”
Section: Fungal Infection In Plants-a Serious Concernmentioning
confidence: 99%
“…Firstly, chlorosis symptoms were appeared on the flowers and also showed that leaves become fall from the branches of the plant. The diseases were controlled by the help of molecular techniques and the chemical treatments [50]. Tagetes erecta is commonly known as the African marigold flowering plant which is cultivated as cosmopolitanly.…”
Section: Fungal Infection In Plants-a Serious Concernmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of D. tulliensis as a fungal pathogen of betel leaves. Diaporthe tulliensis has been reported to cause leaf spots on coffee in China (Gorg et al ., 2020) and on Parthenocissus tricuspidata in Taiwan (Huang et al., 2021), cacao pod rot in Puerto Rico (Serrato‐Diaz et al ., 2022), and stem canker of kiwifruit in China (Bai et al ., 2017) and of jasmine in Taiwan (Hsu et al., 2023).…”
Section: Figurementioning
confidence: 99%
“…Parthenocissus tricuspidata in Taiwan (Huang et al, 2021), cacao pod rot in Puerto Rico (Serrato-Diaz et al, 2022), and stem canker of kiwifruit in China (Bai et al, 2017) and of jasmine in Taiwan (Hsu et al, 2023).…”
Section: And Onmentioning
confidence: 99%